Periodic Wrinkle‐Patterned Single‐Crystalline Ferroelectric Oxide Membranes with Enhanced Piezoelectricity. Issue 50 (2nd November 2020) - Dong, Guohua; Li, Suzhi; Li, Tao; Wu, Haijun; Nan, Tianxiang; Wang, Xiaohua; Liu, Haixia; Cheng, Yuxin; Zhou, Yuqing; Qu, Wanbo; Zhao, Yifan; Peng, Bin; et al.
Abstract: Self‐assembled membranes with periodic wrinkled patterns are the critical building blocks of various flexible electronics, where the wrinkles are usually designed and fabricated to provide distinct functionalities. These membranes are typically metallic and organic materials with good ductility that are tolerant of complex deformation. However, the preparation of oxide membranes, especially those with intricate wrinkle patterns, is challenging due to their inherently strong covalent or ionic bonding, which usually leads to material crazing and brittle fracture. Here, wrinkle‐patterned BaTiO3 (BTO)/poly(dimethylsiloxane) membranes with finely controlled parallel, zigzag, and mosaic patterns are prepared. The BTO layers show excellent flexibility and can form well‐ordered and periodic wrinkles under compressive in‐plane stress. Enhanced piezoelectricity is observed at the sites of peaks and valleys of the wrinkles where the largest strain gradient is generated. Atomistic simulations further reveal that the excellent elasticity and the correlated coupling between polarization and strain/strain gradient are strongly associated with ferroelectric domain switching and continuous dipole rotation. The out‐of‐plane polarization is primarily generated at compressive regions, while the in‐plane polarization dominates at the tensile regions. The wrinkled ferroelectric oxides with differently strained regions and correlated polarization distributions would pave a way toward novel flexible electronics. Abstract : Freestanding BaTiO3 membranes (ferroelastic oxides) and poly(dimethylsiloxane) elastomer (organism) are combined to construct a periodically wrinkled structure. The wrinkle‐patterned ferroelectric membranes offer an ideal platform to explore strain‐correlated fundamental phenomena such as flexoelectricity, strain‐induced ferroelectric domain evolutions, and phase transitions, as well as periodic‐electric‐potential‐induced functions in flexible optical and electrical devices.